Impact Of Covid–19 To Faculty Members of Higher Education Institutions (Hei’s) In Palawan (Eurasian Journal of Learning and Academic Teaching, 2022)
The study focused on the impact of covid-19 to faculty members of Higher Education Institutions (HEI’s) in Palawan. The study employed descriptive forms of statistical tools such as frequency counts, percentages and weighted means. Results showed that the faculty members are middle age, female, married, baccalaureate degree holders, worked for less than ten years with permanent/regular status of appointment, and received a monthly salary between 10,000 t0 49,999. The study revealed that the respondents have high level of awareness when it comes to their cognitive, affective and behavioral about covid-19 pandemic. Respondents assessed themselves mentally, emotionally and behaviorally as in a good state of psychological well – being despite of covid – 19 pandemic.